2010
DOI: 10.1111/j.1460-9568.2009.07065.x
|View full text |Cite
|
Sign up to set email alerts
|

The hypocretin–orexin system regulates cocaine self‐administration via actions on the mesolimbic dopamine system

Abstract: Recent evidence suggests that the hypocretin-orexin system participates in the regulation of reinforcement processes. The current studies examined the extent to which hypocretin neurotransmission regulates behavioral and neurochemical responses to cocaine, and behavioral responses to food reinforcement. These studies used a combination of fixed ratio, discrete trials, progressive ratio and threshold self-administration procedures to assess whether the hypocretin 1 receptor antagonist, SB-334867, reduces cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
300
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(335 citation statements)
references
References 62 publications
29
300
4
1
Order By: Relevance
“…Behavioral economic theory has been successfully applied to drug self-administration in general (Bickel et al, 1993;Hursh, 1991) and TH procedures in particular (Espana et al, 2010;Oleson et al, 2011;Oleson and Roberts, 2009). In the current TH procedure, the descending series of doses (listed above) resulted in rats receiving access to cocaine across the following 11 ascending unit-prices: 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral economic theory has been successfully applied to drug self-administration in general (Bickel et al, 1993;Hursh, 1991) and TH procedures in particular (Espana et al, 2010;Oleson et al, 2011;Oleson and Roberts, 2009). In the current TH procedure, the descending series of doses (listed above) resulted in rats receiving access to cocaine across the following 11 ascending unit-prices: 2.…”
Section: Discussionmentioning
confidence: 99%
“…4, 4.2, 7.5, 13.3, 23.7, 39.9, 75, 134, 242, 417, and 750 responses/mg. The primary dependent measure analyzed was the maximal price paid for cocaine (Pmax), which was determined to be the unit-price corresponding to the apex of the price-response function as previously described (Espana et al, 2010;Oleson et al, 2011). An example of the calculation of Pmax is shown in Figure 4a.…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of the hypocretin system in the rewarding properties of cocaine has mainly been revealed under conditions that require greater degrees of effort and motivation to obtain the drug (28,29). The present data point to a specific role for Hcrtr-1 in the modulation of the reinforcing properties of cannabinoids since the Hcrtr-2 antagonist TCSOX229 did not alter this behavior.…”
Section: The Enhanced Of Dopamine Extracellular Levels In the Nucleusmentioning
confidence: 46%
“…Orexin A has been implicated in anxiety and reward-related behaviors (Buffalari and See, 2010;Dayas et al, 2008;Espana et al, 2010;Harris et al, 2005;Johnson et al, 2010;Lawrence et al, 2006;Richards et al, 2008), and the BNST receives dense orexinergic innervation (Baldo et al, 2003). To test the role of orexin signaling in the effects of yohimbine, we assessed the ability of OxR antagonists to block its actions.…”
Section: Orexin Receptor (Oxr) Antagonists Block Yohimbineinduced Depmentioning
confidence: 99%
“…The orexin system was first described in the late 1990s, when the orexin neuropeptides were shown to be important in feeding and arousal-related behaviors (de Lecea et al, 1998;Sakurai et al, 1998). Since then, studies have demonstrated an important role for the orexin system in anxiety and reward-related behaviors (Boutrel et al, 2005;Dayas et al, 2008;Espana et al, 2010;Harris et al, 2005;Johnson et al, 2010;Lawrence et al, 2006;Richards et al, 2008;Zhou et al, 2011). The BNST receives dense orexinergic inputs (Baldo et al, 2003) and has a high density of OX 1 R mRNA and protein expression (Hervieu et al, 2001;Marcus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%